The emancipatory project of dialectical psychology - Oliveros M., Ricardo (2005)
In this paper aspects of the development of the dialectical psychology are presented as a theoretical-conceptual orientation and as a way of professional practice for psychologists. Ways of expression of dialectical psychology are expose, analyzing and synthesizing key points relating human emancipation. It's an effort for potentate the psychology science with new models, better strategies and more effective instruments. It's considered that the purpose of dialectical psychology is to develop an emancipator project, as an open task with future perspective in the 50th anniversary of psychology in Peru.